2013
DOI: 10.1002/j.2055-2335.2013.tb00249.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral Medication Administration in Patients with Restrictions on Oral Intake—A Snapshot Survey

Abstract: Aim To determine clinical staff's understanding of managing oral medications in patients with restrictions on oral intake. Method An online survey was designed consisting of 4 scenarios featuring a patient who was fasting pre‐surgery, day 1 post‐surgery, nil‐by‐mouth after stroke or had a nasogastric feeding tube in situ. The target population was clinical staff (nursing, medical, pharmacy, dietetics, speech pathology) involved in the management of oral medications and/or patients' oral intake. Medications stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Written feedback or comments were from emails from over 100 staff, with at least 50 from nursing, 20 from medical, 30 from pharmacy, and 15 from other staff including speech language pathologists. Written feedback or comments were also taken from an in‐house survey (unpublished) of intravenous paracetamol use and a medication administration survey because these responses related to the management of oral medications when patients had restrictions on their oral intake. Data were also drawn from an in‐house snapshot audit (unpublished) of medication administration during the period of restriction on patients' oral intake before a surgical procedure.…”
Section: Methodsmentioning
confidence: 99%
“…Written feedback or comments were from emails from over 100 staff, with at least 50 from nursing, 20 from medical, 30 from pharmacy, and 15 from other staff including speech language pathologists. Written feedback or comments were also taken from an in‐house survey (unpublished) of intravenous paracetamol use and a medication administration survey because these responses related to the management of oral medications when patients had restrictions on their oral intake. Data were also drawn from an in‐house snapshot audit (unpublished) of medication administration during the period of restriction on patients' oral intake before a surgical procedure.…”
Section: Methodsmentioning
confidence: 99%
“…Don't rush to crush: modifying oral medicines It has also been shown that knowledge and opinions about medication modification for this patient group vary widely, both across and within the same healthcare profession. [2][3][4][5] Previous studies have examined nursing, medical and pharmacists' approaches to medication modification and administration for these patients; however, this study compares practice directly with the recommendations in SHPA's DRTC Handbook, the current Australian guideline.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] Alarmingly, it was shown in each of these studies that a rel-atively high number of healthcare professionals report cases of inappropriate medication modification and administration, including the crushing of sustained release medications. [2][3][4][5] In addition, medication administration to patients with swallowing difficulties is associated with higher error rates and therefore increased potential for harm, than administering medications to patients without swallowing problems. 6 There are a number of factors that could lead to patients being unable to swallow solid oral medicines in their original form, both physical and psychological.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations